Determinants of unemployment in Asia case study in China, India, Japan, South Korea, and Thailand - Leela Priya, Saminathen; Lee, Jing Min; Lew, Xin Yi; Rivaseni, Nalatamby (2021)
This study seeks to investigate the relationship between unemployment rate (UR), growth of Gross Domestic Product (GDPG), net inflow of Foreign Direct Investment (FDI), population growth (POP), and automation level (AUTO). This study employs secondary data to conduct the panel analysis by using STATA software. The annual panel data is collected from five Asia countries including China, India, Japan, South Korea, and Thailand from 2005 to 2019. The Fixed Effect Model (FEM) is preferred in this study, and results showed GDPG and FDI both have a significant negative relationship with the unemployment rate, while POP has a significant positive relationship with unemployment. However, AUTO is found to be statistically insignificant to affect the unemployment rate. This study also suggested few implications for policymakers in dealing with the unemployment issues such as monetary and fiscal policy, government intervention on the exchange rate, development of infrastructure, child control policy, and others